1998
DOI: 10.1093/nar/26.8.1884
|View full text |Cite
|
Sign up to set email alerts
|

The elongation factor 1 A-2 isoform from rabbit: cloning of the cDNA and characterization of the protein

Abstract: Eukaryotic elongation factor 1 A (eEF1A, formerly elongation factor-1 alpha) is an important component of the protein synthesis apparatus. Here we report the isolation and characterization of the cDNA sequence encoding rabbit eEF1A-2, an isoform of eEF1A, as well as a structural and functional comparison of the two rabbit isoforms. Northern analysis of the expression pattern of eEF1A-2 showed that this isoform is expressed in skeletal muscle, heart, brain and aorta, while transcripts are not detected in liver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 48 publications
4
116
0
1
Order By: Relevance
“…Elongation factor 1-α 2 (EEF1A2) K55 and K165 are known to contain trimethylation by similarity with its ortholog in rabbit, 27 while they were identified as dimethylation sites in our studies. We compared our data to the two other published large-scale lysine acetylation and ubiquitylation data sets.…”
Section: Resultsmentioning
confidence: 58%
“…Elongation factor 1-α 2 (EEF1A2) K55 and K165 are known to contain trimethylation by similarity with its ortholog in rabbit, 27 while they were identified as dimethylation sites in our studies. We compared our data to the two other published large-scale lysine acetylation and ubiquitylation data sets.…”
Section: Resultsmentioning
confidence: 58%
“…We also analyzed the effects of exogenous expression of eEF1A2, a homolog of eEF1A1. 29 In C32 cells, expression of endogenous eEF1A2 was undetectable (Supplementary Figure S3), and exogenous expression of eEF1A2, which inhibits the cell death in tetraploids as well as eEF1A1 (data not shown), was shown to similarly increase the number of binucleated cells (Figure 7b). From these data, the cell death machinery is suggested to contribute to eliminate naturally arising binucleated tetraploid cells.…”
Section: Resultsmentioning
confidence: 89%
“…29 eEF1A2 was reported to be exclusively expressed in brain, heart, and skeletal muscle, whereas eEF1A1 is well known to be ubiquitously expressed. 33 We confirmed that the expression of eEF1A2 was undetectable in cell lines used here (Supplementary Figure S3), suggesting that downregulation of eEF1A1 expression in tetraploid cells generally induces loss of eEF1A expression resulting in severe inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that other factors, such as the M 4 mAChR, may act to regulate nucleotide exchange of eEF1A2 in compartments lacking eEF1B␣. eEF1A2 functions as an essential factor in protein synthesis as demonstrated by its activity in poly(U)-directed polyphenylalanine synthesis assay (38). Its proposed mechanism of action is as follows.…”
Section: Discussionmentioning
confidence: 99%